Identification of Challenges in Integrating Physical Education and Religious Education Curricula - Radmehr, Ali; Talebzadeh Nobrian, Mohsen (Assessment and Practice in Educational Sciences, 2026)
The present study aimed to identify and explain the challenges associated with integrating physical education and religious education curricula from the perspectives of educational experts and practitioners. This study was conducted using a qualitative research design within an interpretivist paradigm, employing grounded theory as the main methodological approach. The research population consisted of experts and teachers with experience in curriculum planning, physical education, and religious education. Participants were selected through purposive and theoretical sampling, and data collection continued until theoretical saturation was achieved. Data were gathered using in-depth semi-structured interviews and analysis of relevant documents. The data analysis process was carried out simultaneously with data collection and followed the systematic procedures of grounded theory, including open coding, axial coding, and selective coding. Constant comparative analysis was used to refine categories and develop a coherent theoretical framework. To ensure the credibility and trustworthiness of the findings, strategies such as member checking, peer review, prolonged engagement, and maintaining an audit trail were applied. The results of the study indicated that the challenges of integrating physical education and religious education curricula can be categorized into four main domains: cultural challenges, content-related challenges, administrative and structural challenges, and methodological challenges. Cultural challenges were identified as the most influential, reflecting deep-rooted attitudinal barriers and resistance to interdisciplinary approaches. Content-related challenges revealed significant issues in resource availability, content organization, balance, and clarity, indicating weaknesses in curriculum design. Administrative and structural challenges highlighted systemic constraints such as centralized curriculum systems, lack of institutional support, and insufficient funding. Methodological challenges pointed to gaps in teaching strategies, lack of appropriate tools, insufficient teacher preparedness, and weak alignment with learners’ needs and real-world contexts. Overall, the findings suggest that these challenges are interrelated and collectively hinder the effective implementation of integrated curricula. The study concludes that successful integration of physical education and religious education curricula requires addressing multidimensional challenges that span cultural, structural, content-related, and methodological domains, and emphasizes the need for systemic reform, enhanced teacher competencies, and context-sensitive curriculum design to achieve meaningful and sustainable integration.